Internet of things for monitoring parking system using optical character recognition - Dona Yuliawati; Rio Kurniawan; Bayu Nugroho; Suhendro Yusuf Irianto; Sri Karnila (JURNAL INFOTEL, 2023)
This research is in the form of an IoT-based parking system, which can help the transportation department. Currently, there are several obstacles experienced in collecting parking levies in the field, the absence of automatic and real-time information on four-wheeled and two-wheeled vehicles and the processing of vehicle parking tax levies is not transparent. One of the components of local revenue is the motor vehicle tax, in Bandar Lampung City, the implementation is still not optimal. This type of On Street Parking parking service uses the curb to park motor vehicles, generally guarded by a parking attendant with a parking location that has been determined by the parking manager. At each On Street Parking parking point, parking attendants are facilitated with a tool in the form of "Monitor Parking", with detection cameras that take pictures of motor vehicle license plates and store them in a database. OCR (Optical Character Recognition) technique of annotated plate data, and generates data again. The design results are in the form of a vehicle parking monitoring tool that can be run through portable gadgets. The "Monitor Parking" tool is easy to use and can help make it easier for parking attendants and the Transportation Agency to monitor parking in the field.